Full-length chloroplast genome of Dongxiang wild rice reveals small single-copy region switching - Liang, Jianguang; Chen, Rui; Zhang, Fantao; Wang, Qian; Yang, Yingxia; Lv, Mingjie; Yan, Shuangyong; Gao, Shan (Frontiers in Plant Science, 2022)
Background: Plant chloroplast DNA (cpDNA) typically has a circular structure, including a large single-copy region (LSC), a small single-copy region (SSC) and two inverted repeats (IR1 and IR2). The organization of these four elementary regions LSC-IR1-SSC-IR2 is highly conserved across all plant cpDNAs. Very few structural variations (SVs) occurring at the elementary-region level have been reported. Results: In the present study, we assembled the full-length cpDNA of Dongxiang wild rice line 159 (DXWR159). Using the long PacBio subreads, we discovered a large inversion of SSC and a large duplication of IR in DXWR159 cpDNAs. Significantly, we reported for the first time forward and reverse SSCs of cpDNAs in similar proportions and named the frequent inversion of a whole SSC as SSC switching. Conclusions: Our study helps researchers to correctly assemble the chloroplast genomes. Our recombination model explained the formation of large SVs in cpDNAs and provided insights into a novel scientific question that if there are common mechanisms in the formation or translocation of all kinds of transposon-like elements (TLEs). We propose that: (1) large inversion is the most accepted mutation type of SVs in cpDNAs; (2) SSC switching ubiquitous occurs in plant cpDNAs; and (3) further investigation of molecular mechanism underlying SSC switching may reveal new driving forces for large SVs.